2006
DOI: 10.1590/s1413-86702006000400004
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of vancomycin resistant enterococci colonization in intensive care patients in a Brazilian teaching hospital

Abstract: Vancomycin-resistant enterococci (VRE) are important pathogens involved in nosocomial infections. Colonization precedes infection and the number of colonized individuals is about 10 times higher than the number of infected patients. We examined VRE colonization in two intensive care units from October 2003 to June 2004. Perirectal swab specimens were obtained from all patients, starting on the 5th day after admission, and then weekly. A total of 249 swabs were obtained from 112 patients. Nine patients had VRE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Demographics characteristics, APACHE II score, and mortality were similar during the pre-and postintervention periods, showing that the population was homogenous during the study period. In contrast with other reports in Brazil, E. faecium was the most frequent specie of VRE identified in our hospital and the vanA gene was identified in all strains causing infection [16][17][18].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Demographics characteristics, APACHE II score, and mortality were similar during the pre-and postintervention periods, showing that the population was homogenous during the study period. In contrast with other reports in Brazil, E. faecium was the most frequent specie of VRE identified in our hospital and the vanA gene was identified in all strains causing infection [16][17][18].…”
Section: Discussioncontrasting
confidence: 98%
“…VRE was first described in Brazil in 1996 [16]. Variation in the prevalence of colonization among Brazilian hospitals is high, with reported rates from 0 to 33% [16][17][18]. In the present study, the rate of colonization ranged in the baseline period from 1.99 to 36.29 colonized patients per 1,000 patient-days.…”
Section: Discussionmentioning
confidence: 55%
“…In High-level gentamicin-resistant E. faecalis bacteremia www.bjournal.com.br addition, our results emphasize the need for strategies to improve infection-control practices, such as judicious use of antibiotics and monitoring of antibiotic resistance among hematologic patients. This could prevent further dissemination of HLGR, allow the monitoring of changes in enterococcal resistance patterns, and ultimately prevent the spread of VRE at our institution, which is currently limited to a few cases of colonization (20).…”
Section: Discussionmentioning
confidence: 99%
“…These rates are among the highest reported in Europe. Fecal colonization of VRE was found that 1.4% of hospitalized patients in The Netherlands 17 , 3.5% in Belgium 18 , 8% in Brazil 19 . The authors hypothesized that this was related to the limited use of glycopeptide antibiotics, the absence of cross-contamination, structured surveillance program.…”
Section: Discussionmentioning
confidence: 99%